2023
DOI: 10.3390/clinpract13030052
|View full text |Cite
|
Sign up to set email alerts
|

Fast Track Protocols and Early Rehabilitation after Surgery in Total Hip Arthroplasty: A Narrative Review

Abstract: The Enhanced Recovery After Surgery (ERAS) or Fast Track is defined as a multi-disciplinary, peri- and post-operative approach finalized to reduce surgical stress and simplify post-operative recovery. It has been introduced more than 20 years ago by Khelet to improve outcomes in general surgery. Fast Track is adapted to the patient’s condition and improves traditional rehabilitation methods using evidence-based practices. Fast Track programs have been introduced into total hip arthroplasty (THA) surgery, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 142 publications
0
0
0
Order By: Relevance
“…Abundance of scientific literature about the risks and benefits of DAA pushed towards the implementation of DAA at the Authors' institution. Indeed, many studies showed that early postoperative functional recovery was faster [21] when compared to other approaches [22,23], recognizing that after a few months the differences in functional recovery disappear [24,25]. In fact, in the prospective randomized clinical study by Barrett et al [24], THAs performed by DAA and PL approach were compared, and they showed how post-operative recovery was faster with DAA in the first 6 weeks after surgery, although differences completely disappeared at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Abundance of scientific literature about the risks and benefits of DAA pushed towards the implementation of DAA at the Authors' institution. Indeed, many studies showed that early postoperative functional recovery was faster [21] when compared to other approaches [22,23], recognizing that after a few months the differences in functional recovery disappear [24,25]. In fact, in the prospective randomized clinical study by Barrett et al [24], THAs performed by DAA and PL approach were compared, and they showed how post-operative recovery was faster with DAA in the first 6 weeks after surgery, although differences completely disappeared at 6 months.…”
Section: Discussionmentioning
confidence: 99%